The Authority of the Indonesia Deposit Insurance Corporation to Initiate Bankruptcy Proceedings against Controlling Shareholders of Non-Systemic Failed Banks: Reconstructing Personal Liability within the Indonesian Banking Law Regime - Diana R.W. Napitupulu (Jurnal Smart Hukum (JSH), 2026)
This article examines the legal authority of the Indonesia Deposit Insurance Corporation (Lembaga Penjamin Simpanan/LPS) to initiate bankruptcy proceedings against controlling shareholders of non-systemic failed banks, focusing on the reconstruction of personal liability within the Indonesian banking law regime. The study departs from the prevailing scholarly focus on bank resolution mechanisms and institutional liability, addressing a normative gap concerning the personal accountability of controlling shareholders whose actions contribute to bank failure and subsequent losses borne by LPS. Using a normative juridical method with statutory, conceptual, and doctrinal approaches, this research analyzes the interplay between the Law on Deposit Insurance Corporation, Banking Law, Company Law, and Bankruptcy Law. The findings demonstrate that LPS possesses legal standing as a creditor by virtue of subrogation after fulfilling its statutory obligation to pay insured deposits. This status provides a legitimate basis for LPS to pursue bankruptcy claims not only against failed banks but also against controlling shareholders, provided that their factual control, unlawful conduct, or gross negligence can be established as the proximate cause of the bank’s failure and the depletion of insured funds. The article further argues that the principle of limited liability is not absolute and may be lawfully pierced through a causality-based construction of personal responsibility consistent with the doctrine of piercing the corporate veil. This study proposes a reconstructed legal framework that articulates objective parameters for imposing personal bankruptcy liability on controlling shareholders, thereby preventing arbitrary enforcement while strengthening the protection of public funds administered by LPS. By integrating banking law, corporate law, and bankruptcy law, this article contributes a novel analytical model that enhances legal certainty, judicial consistency, and the effectiveness of asset recovery in cases of non-systemic bank failure in Indonesia.